2005
DOI: 10.4028/www.scientific.net/ssp.108-109.17
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Precipitation in Nitrogen Doped CZ Silicon

Abstract: Nitrogen doping of CZ silicon results in an early formation of large precipitate nuclei during crystal cooling, which are stable at 900°C. These are prone to develop stacking faults and high densities of defects inside defect denuded zones of CZ silicon wafers. Simultaneous doping of FZ silicon with nitrogen and oxygen results in two main stages of precipitate nucleation during crystal cooling, an enhanced nucleation around 800°C, which is nitrogen induced, and a second enhancement around 600°C, which depends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Ramping from 500 °C reveals most of the grown-in oxide precipitate nuclei [21]. In a previous paper, we have also shown that this BMD profile follows the theoretically simulated v/G profile, what means that it follows the vacancy supersaturation [23]. This indicates that the concentration of intrinsic point defects is of strong impact on the density of grown-in nuclei.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Ramping from 500 °C reveals most of the grown-in oxide precipitate nuclei [21]. In a previous paper, we have also shown that this BMD profile follows the theoretically simulated v/G profile, what means that it follows the vacancy supersaturation [23]. This indicates that the concentration of intrinsic point defects is of strong impact on the density of grown-in nuclei.…”
Section: Resultssupporting
confidence: 72%
“…A RATOC MILSA IRHQ-2 light scattering tomograph with a Nd-YAG Laser (1060 nm wavelength) was used for the LST measurements. CZ reference wafer grown under similar pulling conditions [23]. These large grown-in precipitate nuclei in NCZ silicon can easily grow during thermal processing making the generation of bulk micro-defects for internal gettering very easy.…”
Section: Methodsmentioning
confidence: 99%